2010
DOI: 10.1001/archpediatrics.2010.130
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Midazolam vs Rectal Diazepam for the Home Treatment of Acute Seizures in Pediatric Patients With Epilepsy

Abstract: Objective: To compare intranasal midazolam, using a Mucosal Atomization Device (IN-MMAD), with rectal diazepam (RD) for the home treatment of seizures in children with epilepsy.Design: Prospective randomized study.Setting: Patients' homes and a freestanding children's hospital that serves as a referral center for 5 states.Patients: A total of 358 pediatric patients who visited a pediatric neurology clinic from July 2006 through September 2008 and were prescribed a home rescue medication for their next seizure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 41 publications
1
127
0
3
Order By: Relevance
“…No one trial has focused solely on comparing the adverse drug reactions of intranasal midazolam to rectal diazepam, but useful information can be extrapolated from several past studies. 1,8,12,16,17 A prospective, randomized trial by Holsti and colleagues 1 found no detectable difference in the number of adverse drug reactions among the intranasal midazolam and rectal diazepam groups. Occurrence of repeated seizure within 12 hours, need for ED services, and respiratory depression rates were similar.…”
Section: Safetymentioning
confidence: 99%
See 4 more Smart Citations
“…No one trial has focused solely on comparing the adverse drug reactions of intranasal midazolam to rectal diazepam, but useful information can be extrapolated from several past studies. 1,8,12,16,17 A prospective, randomized trial by Holsti and colleagues 1 found no detectable difference in the number of adverse drug reactions among the intranasal midazolam and rectal diazepam groups. Occurrence of repeated seizure within 12 hours, need for ED services, and respiratory depression rates were similar.…”
Section: Safetymentioning
confidence: 99%
“…Prospective and retrospective evidence shows that intranasal midazolam terminates seizures at least as fast as rectal diazepam. 1,5,8,[12][13][14][15] Most clinical studies have used a 5 mg/mL midazolam solution dosed at 0.2 mg/ kg (divided into each nostril) administered via an intranasal mucosal atomization (IN-MADD) device or nasal dropper as suggested by Kyrkou and colleagues. 16 Three open-labeled studies prospectively evaluated the time to seizure cessation with a dose of nasal midazolam (Table).…”
Section: Time To Seizure Cessationmentioning
confidence: 99%
See 3 more Smart Citations